KOMPETENSI KEPALA DAERAH DALAM PELAYANAN PUBLIK PEMERINTAH PROVINSI SULAWESI SELATAN - Rudi Salam; Sudiarti Sudiarti; Aris Baharuddin; Denok Sunarsi (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2022)
The results of the study indicate that it can be concluded how low the quality of service in the South SulawesiProvincial Government is, even though the demand for the quality and quantity of public services by usersis increasing. The use has paid for public services, but the desired quality and quantity have not been met.Transparency of accountability in public services is needed to overcome the gap between the parties involvedin public services, so that regulators are also required to be able to allocate existing resources and there isa balance between the parties involved in public services. Apart from the use of public services (non-users),it is necessary to pay attention to its importance, especially the demands of the strategic environment.Until now, public services still have various weaknesses, including: less responsive, less informative, lessaccessible, lack of coordination, and bureaucracy where licensing services are generally carried out througha process consisting of various levels so that it is too long. In addition, public services are also less willingto listen to community complaints/suggestions/aspirations and are inefficient